Building a winning sales force powerful strategies for driving high performance - Zoltners, Andris A. (AMACOM, 2009)
"A high-performance sales force is one of the most critical components of any successful organization. But it is also a complex organism that is difficult to understand-and therefore extremely challenging to develop and lead." "Building a Winning Sales Force is the most comprehensive and practical book ever written on the subject of designing, building, and driving a superior sales team. The book combines the wisdom and advice of three renowned sales experts whose experience ranges from the university classroom to the boardrooms of more than 400 sales organizations around the world." "With this book as your guide, you will learn the changes to implement now that will immediately enhance the performance of all your sales professionals while also building new customer relationships, and, of course, driving your top and bottom line results - all without disrupting your current sales progress."--Jacket.